Kegiatan Pengabdian Masyarakat dengan Edukasi dan Skrining Kadar Air, Kadar Minyak, dan Hidrasi Kulit pada Kelompok Usia Remaja di SMA Kalam Kudus 2 - Catharina Sagita Moniaga; Alexander Halim Santoso; Eric Hartono; Louise Audrey Sukianto; Tosya Putri Alifia; Edwin Destra (STIKes Ibnu Sina Ajibarang, 2024)
Healthy skin is a condition in which the skin’s moisture, oil levels, and elasticity are optimally maintained, allowing it to protect the body from external factors and maintain its physiological balance. The balance of water, oil, and skin hydration is especially important for adolescents undergoing hormonal changes. The purpose of this activity is to enhance adolescents' awareness and understanding of the importance of healthy skin through education and assessments of some of the skin contents. This community service activity was organized using the Plan-Do-Check-Act (PDCA) method, which includes health education and assessments of skin water, oil, and hydration levels among adolescent groups. The results of this activity indicate that screening and education contribute to adolescents’ understanding of the risk factors affecting skin health, the importance of appropriate skincare, and the benefits of regular assessments. The activity's discussion highlights that balanced levels of water, oil, and skin hydration play a role in preventing skin issues such as infections, acne, dermatitis, and premature aging. This education supports adolescents in adopting healthy habits to maintain their skin health. This activity plays a crucial role in raising adolescents' awareness of skin health, thereby reducing the risk of future skin disorders.